Perspectives on implementing mobile health technology for living kidney donor follow‐up: In‐depth interviews with transplant providers. Issue 8 (1st July 2019) - Eno, Ann K.; Ruck, Jessica M.; Van Pilsum Rasmussen, Sarah E.; Waldram, Madeleine M.; Thomas, Alvin G.; Purnell, Tanjala S.; Garonzik Wang, Jacqueline M.; Massie, Allan B.; Al Almmary, Fawaz; Cooper, Lisa M.; Segev, Dorry L.; Levan, Michael A.; et al.
Abstract: Background: United States transplant centers are required to report follow‐up data for living kidney donors for 2 years post‐donation. However, living kidney donor (LKD) follow‐up is often incomplete. Mobile health (mHealth) technologies could ease data collection burden but have not yet been explored in this context. Methods: We conducted semi‐structured in‐depth interviews with a convenience sample of 21 transplant providers and thought leaders about challenges in LKD follow‐up, and the potential role of mHealth in overcoming these challenges. Results: Participants reported challenges conveying the importance of follow‐up to LKDs, limited data from international/out‐of‐town LKDs, and inadequate staffing. They believed the 2‐year requirement was insufficient, but expressed difficulty engaging LKDs for even this short time and inadequate resources for longer‐term follow‐up. Participants believed an mHealth system for post‐donation follow‐up could benefit LKDs (by simplifying communication/tasks and improving donor engagement) and transplant centers (by streamlining communication and decreasing workforce burden). Concerns included cost, learning curves, security/privacy, patient language/socioeconomic barriers, and older donor comfort with mHealth technology. Conclusions: Transplant providers felt that mHealth technology could improve LKD follow‐up and help centers meet reporting thresholds. However, designing a secure, easy to use, and cost‐effective system remains challenging.